Ekokardiografi pada Gagal Jantung - Rahmianti, Nia Dyah; Trisna, Ni Putu Alit (MEDICINUS, 2020)
Heart failure (HF) is a leading cause of cardiovascular morbidity and mortality worldwide. Clinical diagnosis of HF is often challenging because the symptoms and signs of HF are either too nonspecific or too infrequent. Echocardiography, given its safety, easy availability, and the ability to permit a comprehensive assessment of cardiac structure and function, is an indispensable tool in the evaluation and management of patients with heart failure (HF). It can also detect and define the hemodynamic and morphologic changes in HF over time and might be equivalent to invasive measures in guiding therapy. The early detection of heart failure has been facilitated by the assessment of global longitudinal strain, which is also useful in later heart failure for the assessment of left ventricular synchrony.The use of echocardiography has been associated with favorable outcomes, probably onthe basis of facilitation of appropriate therapy. Although the guidelines emphasize that no singletest satisfies all imaging requirements in heart failure, and other modalities can provide additional information about specific questions (especially tissue characterization), echocardiography is indispensable in the management of heart failure.